2019
DOI: 10.7554/elife.50063
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila PSI controls circadian period and the phase of circadian behavior under temperature cycle via tim splicing

Abstract: The Drosophila circadian pacemaker consists of transcriptional feedback loops subjected to post-transcriptional and post-translational regulation. While post-translational regulatory mechanisms have been studied in detail, much less is known about circadian post-transcriptional control. Thus, we targeted 364 RNA binding and RNA associated proteins with RNA interference. Among the 43 hits we identified was the alternative splicing regulator P-element somatic inhibitor (PSI). PSI regulates the thermosensitive al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…This agrees with the transcriptomic analysis of a recent publication that reveals an upregulation of eya in flies exposed to short photoperiod (10 L:14D) at 11°C for 3 wk when compared to reproductively active condition (25°C, 12 L:12D) (65). In light of the recent evidence on tim thermosensitive alternative splicing (37,38,66), we were able to confirm the induction of the tim-sc mRNA and protein at 10°C. Consistent with our model, our results support the prevalent role of the cold-induced TIM-SC isoforms in stabilizing EYA under low temperature and suggest that TIM thermosensitive splicing mechanism plays a role in regulating seasonal physiology.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with the transcriptomic analysis of a recent publication that reveals an upregulation of eya in flies exposed to short photoperiod (10 L:14D) at 11°C for 3 wk when compared to reproductively active condition (25°C, 12 L:12D) (65). In light of the recent evidence on tim thermosensitive alternative splicing (37,38,66), we were able to confirm the induction of the tim-sc mRNA and protein at 10°C. Consistent with our model, our results support the prevalent role of the cold-induced TIM-SC isoforms in stabilizing EYA under low temperature and suggest that TIM thermosensitive splicing mechanism plays a role in regulating seasonal physiology.…”
Section: Discussionsupporting
confidence: 91%
“…At 10 °C, canonical TIM was barely detectable using our TIM antibody when compared to TIM levels at 25 °C, and no other isoforms were detected. Concomitantly, recent studies revealed that tim undergoes a thermosensitive alternative splicing controlling the relative abundance of various tim isoforms ( 37 , 38 ). Consistent with our observation, the authors found lower levels of the canonical TIM protein at 18 °C and revealed the induction of two cold-specific splice forms ( tim-cold and tim-short&cold ).…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with the transcriptomic analysis of a recent publication that reveals an upregulation of eya in flies exposed to short photoperiod (10 L:14D) at 11°C for 3 weeks when compared to reproductively active condition (25°C, 12 L:12D) (65). In light of the recent evidence on tim thermosensitive alternative splicing (37, 38, 66), we were able to confirm the induction of the tim-sc mRNA and protein at 10°C. Consistent with our model, our results support the prevalent role of the cold-induced TIM-SC isoforms in stabilizing EYA under low temperature and suggest that TIM thermosensitive splicing mechanism plays a role in regulating seasonal physiology.…”
Section: Discussionsupporting
confidence: 52%
“…In Drosophila, period (PER) and timeless (TIM) protein and mRNA products undergo daily fluctuations in relation to the circadian clock [ 66 , 71 , 73 , 74 , 77 ]. Majercak et al showed that temperature-dependent alternative splicing in the PER gene plays a key role in adaptation of a circadian clock to seasonally cold days (low temperatures and short day lengths) in Drosophila [ 73 ].…”
Section: Regulation Of Gene Expression By Temperature-dependent Almentioning
confidence: 99%
“…Foley et al demonstrated that the alternative splicing regulator P-element somatic inhibitor (PSI) regulates the temperature-dependent alternative splicing of TIM in Drosophila, regulating the period of circadian rhythms and circadian behavior phase during temperature cycling [ 77 ].…”
Section: Molecular Mechanism Of Temperature-dependent Alternative mentioning
confidence: 99%